The state-building process of Post-Soviet Armenia - Danielyan, Hamazasp (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2008)
Two thirds of ethnic Armenians live outside of Armenia. Armenian communities are scattered throughout the world - from Canada to Australia and from Argentina to Siberia. The genesis of the Armenian Diaspora ("Spyurq") started in the Middle Ages, but the majority of Armenian exodus from their homeland occurred as a result of two events: the 1915 Genocide in Western Armenia carried out by the Government of the Young Turks, and the Sovietization of Eastern Armenia (1920) which was previously part of the Russian Empire. Despite the chain of events, and the wide geographic range of emigration they caused, Armenian communities have developed and sustained themselves globally.The aim of this paper is (1) to evaluate the influence of Diaspora on the state building process in the newly independent Republic of Armenia and (2) to analyze the Government of Armeniaćs (GoA) position on the inclusion of the Diaspora in the Armenian political processes. The historical perception of Diasporan politics towards Armenia will be presented first, including the role of the Diasporan political parties in reinventing the independence and building new statehood in Armenia at the end of 1980s and the beginning of 1990s. Since independence, relations between Armenia and the Diaspora have evolved through more than a decade long intensive interactions. The opportunity to obtain dual citizenship was proposed to Diasporan Armenians through amendments made to the Constitution of Armenia in 2005. Despite this action, it remains unclear to what extent Diasporan Armenians are committed to repatriation or a stronger presence in the political life of Armenia. This paper will then focus on a case study of Diasporan organizations' reaction to the post-electoral developments that unfolded in Armenia in February-March 2008.
Keywords: Armenija; državnost; etnični odnosi; diaspora; demokratizacija